Cryostorage of immature and mature human testis tissue to preserve spermatogonial stem cells (SSCs): a systematic review of current experiences toward clinical applications - Pourhabibi Zarandi N (Dove Medical Press, 2018)
Nima Pourhabibi Zarandi,1,* Guillermo Galdon,1,* Stanley Kogan,1,2 Anthony Atala,1,2 Hooman Sadri-Ardekani1,2 1Wake Forest Institute for Regenerative Medicine, Wake Forest School of Medicine, Winston-Salem, NC, USA; 2Department of Urology, Wake Forest School of Medicine, Winston-Salem, NC, USA *These authors contributed equally to this work Abstract: While the survival rate of children with cancer is increasing, preserving fertility for prepubertal boys is still a challenge. Although intracytoplasmic sperm injection (ICSI) using frozen sperms has revolutionized infertility treatment, it is not applicable for the patients who undergo chemotherapy before puberty since spermatogenesis has not begun. Therefore, preserving spermatogonial stem cells (SSCs) as an experimental option can be provided to prepubertal patients at a risk of damage or loss of their SSCs due to cancer treatments and developmental or genetic disorders. Using frozen SSCs in testicular tissue, successful SSC autotransplantation in mouse and nonhuman primates has shown a promising future for SSC-based cell therapy. Cryopreservation of testicular tissue containing SSCs is the first step to translate SSC-based cell therapy into clinical male infertility treatment, and in the investigation into SSCs, it is very important to evaluate their quantity and functionality during this process. This systematic review summarizes the published data on cryopreservation techniques in human testis tissue for potential utilization in future clinical applications. Keywords: testis, spermatogonial stem cell, tissue banking, cryopreservation, male infertility, transplantation